SIFAT EKSTRAK KULIT ACACIA DECURRENS SEBAGAI INSEKTISIDA (Antitermitic Properties from: Acacia decuerena ,Bark ExtractilHIB) - Gustan Pari (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
creening triala were cond.ucted to determine. t , antitermitic properties. of methanol:dieth.yl ether:ethyl acetate (M:D:E) and acetone:diethylether:ethyl acetate (A:Dfg) tannin extract obtained from Acaciadeeurrens bark. The eoa- centration for eaolt>treatmentare 0,10 and'0,14 g/ml, and Cryptotennes cynocephalus Light termite were uaed to evaluate antiter:miticproperties.TM rault ahowa that complete termite mortality occured on methanol:diethyt ether:ethyl acetate. Nearly Complete mortality occurred on acetone:diethyl:ethyl ether:ethyl acetate and the filtrat from each soluent is also still toxic.i